Anxiolytic-like Effect of Luma chequen Essential Oil: A Pilot Study - Alvarado-García, Paul Alan Arkin (2021)
Introduction: Essential oils are complex substances used widely extended in the form of aromatherapy or phytotherapy, some of them as agents to relieve anxiety and stress. In this sense this study was conducted to examine the anxiolytic-like effect of Luma chequen essential oil. Methods: The essential oil was extracted by steam distillation and the chemical composition was investigated by Gas chromatography with flame-ionization detection (GC-FID) and Gas chromatography-mass spectrometry (GC–MS). Moreover, a randomized, double blind, placebo-controlled trial was conducted, where 48 participants were divided into two groups, comprising a control group (CG) treated with placebo, and an experimental group (EG) treated with aromatherapy based on Luma chequen essential oil. The anxiety index was evaluated by State-Trait Anxiety Inventory (STAI). Measures were taken at two times: pretest and posttest. Results: The chemical analysis showed that α-pinene was the main component (56.5%). State and Trait anxiety scores showed a decrease in posttest study phase in comparison with pretest in experimental group compared to placebo (p<0.005 for state anxiety and p<0.05 for trait anxiety). Cohen`s d score was 0.84 in State anxiety, while it was 0.52 for Trait anxiety. Percentages of change showed reductions of anxiety variable ranging between 14.94% for State anxiety and 13.60% for Trait anxiety. Conclusions: These results suggest that aromatherapy based on essential oil of Luma chequen was moderately effective in improving anxiety.